Perbandingan Percutaneous Nephrolithotomy (PCNL) dan Open Nephorlithotomy Pada Pasien dengan Batu Staghorn : Systematic Review - Ramadhan, Ilham; Wibisono, Wibisono (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2025)
Introduction: Staghorn stones are one of the most severe forms of urinary lithiasis. They have a nuclear body and at least one calyceal branch. Untreated staghorn stones are associated with recurrent infections, stone growth, significant morbidity, and progressive loss of renal function. This requires further development of appropriate management, both open surgical and endourological. Objective: to compare percutaneous nephrolithotomy (PCNL) and open nephrolithotomy in patients with staghorn stones. Methods: This review was conducted in accordance with the requirements outlined in PRISMA 2020. A systematic search for studies to be included in the review was conducted from 20 February 2025 using GoogleScholar, PubMed and SagePub databases using the words: